Sheep Breeding and the Production of Sheep’s Milk in Poland and the World - Ptasińska-Marcinkiewicz, Joanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
This paper presents the status and development prospects of sheep breeding in Poland and the world. Sheep farming is practiced in many countries, and in some is of particular economic importance. The largest sheep herds are kept in China, India, Australia, Sudan, and, in Europe, in the United Kingdom, France, Italy, Spain and Greece. In Poland, there has been a drastic reduction in the number of sheep since 1990. The current sheep population is only about 5% of what it was in the 1980s. For this reason, and in agreement with world trends and parallel to action taken at the EU level, national aid programmes aimed at maintaining and restoring the numbers of these animals have been implemented in recent years. In regions where the tradition of sheep farming has existed for centuries, financial assistance is provided at regional level as well.